The effect of Silver addition and deformation parameters on mechanostructure, biodegradation, antimicrobial and mechanical properties of Zn-based biodegradable alloys - Aksakal, Buenyamin; Sezek, Sinan; Macit, Cevher Kursat (Sage Publications Ltd, 2024)
Although low mechanical properties, Zinc (Zn) alloy systems with Copper (Cu) and Silver (Ag) as alloying elements have strong biocompatibility and biodegradability characteristics. This study examined the effects of rolling parameters and Ag alloying on the mechanical, biodegradable, and final structure of an alloy based on Zn. Comparing treated and untreated specimens, the addition of Ag led to a considerable improvement in both hardness and compressive strength. The produced alloys with varying amounts of Ag (between 1 and 4 wt%) were cold rolled at 400-800 r/min and friction coefficients between 0.3 and 0.5. The alloys' ultimate strength rose with an increase in rolling speed for Zn1Cu4Ag, and hardness and compressive strengths rose to 80HV and 470 MPa, respectively. It was demonstrated that rolling force rose somewhat with Ag concentration but significantly increased with rolling speed and friction. E. Coli and S. aureus were used to assess the biodegradable alloys' antibacterial properties. For the Zn-1Cu-2Ag alloy, the inclusion of Ag resulted in a considerable (50%) rise in antibacterial activity that exceeded the effects seen in other alloy systems.
Keywords: Biodegradable materials; biodegradation; antibacterial activity; rolling; mechanostructure